Comprehensive Analysis of Quantitative Proteomics With DIA Mass Spectrometry and ceRNA Network in Intrahepatic Cholestasis of Pregnancy - Fang, Dajun; Fang, Yan; Zhang, Weiqiang; Xiang, Yun; Cheng, Xi; Liang, Mingfeng; Xia, Huimin (Frontiers in Cell and Developmental Biology, 2022)
Background: Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-specific complication characterized by pruritus without skin damage and jaundice. The poor perinatal outcomes include fetal distress, preterm birth and unexpected intrauterine death. However, the mechanism of ICP leading to poor prognosis is still unclear. Methods: We analyzed 10 ICP and 10 normal placenta specimens through quantitative proteomics of data-independent acquisition (DIA) to screen and identify differentially expressed proteins. GO, KEGG, COG/KOG, StringDB, InterProScan, Metascape, BioGPS and Networkanalyst databases were used in this study. PITA, miRanda, TargetScan, starBase and LncBase Predicted v.2 were used for constructing competing endogenous RNA (ceRNA)network. Cytoscape was used for drawing regulatory networks and cytoHubba was used for screening core nodes. The ICP rat models were to validate pathological mechanism. Results: GO, KEGG and COG/KOG functional enrichment analysis results showed the differentially expressed proteins participated in autophagy, autophagosome formation, cofactor binding, JAK-STAT signaling pathway and Coenzyme transport and metabolism. DisGeNET analysis showed these differentially expressed proteins were associated with Red blood cell disorder and Slow progression. We further analyzed first 12 proteins in the up-regulated and down-regulated differentially expressed proteins, and incorporating clinicopathological parameters, our results showed HBG1, SPI1, HBG2, HBE1, FOXK1, KRT72, SLC13A3, MBD2, SP9, GPLD1, MYH7 and BLOC1S1 were associated with ICP development. CeRNA network analysis showed that MBD2, SPI1, FOXK1, SLC13A3 was regulated by multiple miRNAs and LncRNAs. Conclusion: ICP was associated with autophagy. CeRNA network of MBD2, SPI1, FOXK1 and SLC13A3 were involved in ICP progression and these core proteins might be potential target.